Fundamentals of engineering electromagnetics - Cheng, David K. (Massachusetts : Addision-Wesley Publishing Company, 1993)
The book has been developed in response to the need for a text that supports the mastery of this difficult subject. Therefore, in addition to presenting electromagnetics in a concise and logical manner, the text includes end-of-section review questions, worked examples, boxed remarks that alert students to key ideas and tricky points, margin notes, and point-by-point chapter summaries. Examples and applications invite students to solve problems and build their knowledge of electromagnetics. Application topics include: electric motors, transmission lines, waveguides, antenna arrays and radar systems.
1. The Electromagnetic Model. Overview. The electromagnetic model. SI units and universal constants. Summary.2. Vector Analysis. Overview. Vector addition and subtraction. Vector multiplication. Orthogonal coordinate systems. Gradient of a scalar field. Divergence of a vector field. Divergence theorem. Curl of a vector field. Stoke's theorem. Two null identities. Field classification and Helmholtz's theorem. Summary. Problems.3. Static Electric Fields. Overview. Fundamental postulates of electrostatics in free space. Coulomb's law. Gauss's law and applications. Electric potential. Material media in static electric field. Electric flux density and dielectric constant. Boundary conditions for electrostatic fields. Capacitances and capacitors. Electrostatic energy and forces. Solution of electrostatic boundary-value problems. Summary. Problems.4. Steady Electric Currents. Overview. Current density and Ohm's law. Equation of continuity and Kirchoff's current law. Power dissipation and Joule's law. Governing equations for steady current density. Resistance calculations. Summary. Problems.5. Static Magnetic Fields. Overview. Fundamental postulates of magnetostatics in free space. Vector magnetic potential. The Biot-Savart law and applications. The magnetic dipole. Magnetization and equivalent current densities. Magnetic field intensity and relative permeability. Behavior of magnetic materials. Boundary conditions for magnetostatic fields. Inductances and inductors. Magnetic energy. Magnetic forces and torques. Summary. Problems.6. Time-Varying Fields and Maxwell's Equations. Overview. Faraday's law of electromagnetic induction. Maxwell's equations. Potential functions. Time-harmonic fields. Summary. Problems.7. Plane Electromagnetic Waves. Overview. Plane waves in lossless media. Plane waves in lossy media. Group velocity. Flow of electromagentic power and the poynting vector. Normal incidence of plane waves at plane boundaries. Oblique incidence of plane waves at plane boundaries. Summary. Problems.8. Transmission Lines. Overview. General transmission-line equations. Transmission-line parameters. Wave characteristics on an infinite transmission line. Wave characteristics on finite transmission lines. The Smith chart. Transmission-line impedance matching. Summary. Problems.9. Waveguides and Cavity Resonators. Overview. General wave behaviors along uniform guiding structures. Rectrangular waveguides. Other waveguide types. Cavity resonators. Summary. Problems.10. Antennas and Antenna Arrays. Overview. The elemental electric dipole. Antenna patterns and directivity. Thin linear antennas. Antenna arrays. Effective area and backscatter cross section. Friis transmission formula and radar equation. Summary. Problems.Appendix A: Symbols and Units. Appendix B: Some Useful Material Constants. Bibliography. Answers to Odd-numbered Problems. Index. Back Endpapers.
Includes bibliographical references and index.
Keywords: ELECTRICAL ENGINEERING